2019
DOI: 10.1155/2019/5856080
|View full text |Cite
|
Sign up to set email alerts
|

Explosion‐Induced Stress Wave Propagation in Interacting Fault System: Numerical Modeling and Implications for Chaoyang Coal Mine

Abstract: Exploring the propagation of stress waves in rocks with preexisting discontinuities is of great importance to reveal rock and geological engineering problems, particularly dynamic disasters like earthquakes and rockbursts in underground coal mining. In this paper, six 3D models established with COMSOL Multiphysics are employed to explore the influence of two preexisting faults with different orientations on the propagation process of explosion-induced stress waves and the reflection effect. Considering the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…When the stress wave passes through the fault, part of the energy of the stress wave will be absorbed by the fault, resulting in obvious attenuation of dynamic response, and the angle of the fault has a great impact on this phenomenon 15 . During the propagation of stress wave, due to the existence of fault, the reflection effect of stress wave will also occur 16 , which intensifies the damage of rock mass in the area between fault and fault 17 , 18 . The structure of weak interlayer is similar to that of fault.…”
Section: Introductionmentioning
confidence: 99%
“…When the stress wave passes through the fault, part of the energy of the stress wave will be absorbed by the fault, resulting in obvious attenuation of dynamic response, and the angle of the fault has a great impact on this phenomenon 15 . During the propagation of stress wave, due to the existence of fault, the reflection effect of stress wave will also occur 16 , which intensifies the damage of rock mass in the area between fault and fault 17 , 18 . The structure of weak interlayer is similar to that of fault.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies consider the coupling effect of joint characteristics and stress field. The study shows that the joints under confining pressure can attenuate to a specific extent corresponding to the force waves [20,21]. As a result, the author considers the qualities of the filling joint material under the joint influence conditions and the coupling impact of various confining pressure levels.…”
Section: Introductionmentioning
confidence: 99%
“…The average deformation of the advanced headings in the working face has been controlled [20]. Feng et al [21] used COMSOL to study the influence of faults on stress wave propagation and indicated that the elastic modulus, density, and Poisson's ratio of the fault surrounding rock significantly influence stress wave attenuation. He et al [22] studied seismic wave propagation due to a remote seismic source and found that the seismic wave attenuates more rapidly in weaker rock formations.…”
Section: Introductionmentioning
confidence: 99%